Acting in the context of feature films - Barnych, Mykhailo M.; Gavran, Iryna A.; Hrubych, Kostiantyn V.; Medvedieva, Alla O.; Kravchenko, Tetiana O. (Linguistics and Culture Review, 2021)
Acting is an ancient art form that has existed since time immemorial. Acting as a creative activity is one of several types of performing arts, and they all have three common phases of development; training/preparation, rehearsal/practice and performance. In addition, any study of the performing arts must take into account the reality that a performer is always embedded in the contextual environment and participates in one or more of the three phases of development. Acting in modern cinema remains an activity that involves instantaneous interaction with others, while maintaining the ability to draw from personal past experiences and imaginations about oneself, others and/or the environment. The purpose of this study was to identify the features of acting in cinema and to identify the difference with the work in the theatrical environment. The main methods of this study were analysis and comparison. Although theatrical and cinematographic traditions represent stylistic and aesthetic differences, the actor's training and the concepts of the play are more similar than contradictory. What crosses time, culture and the environment is the need to train the actor.